Effectiveness of Powtoon Learning Media in Increasing Students' English Grammar Knowledge - Darmawati, Darmawati (Journal of Education Method and Learning Strategy, 2023)
The purpose of this study was to ascertain how Pow Toon learning materials work to improve students' English grammar knowledge. This study was carried out in Medan, Indonesia. Twenty eighth-grade kids served as the study's participants. Using Pow Toon learning resources, students' results on the English Grammar (basic present tense) test increased with each test. The pre-test had an average score of 57.66, the first cycle's test had an average of 74.33, and the second cycle's exam had an average of 90.66. The percentage of students passing their English Grammar tests (simple present tense) shows an increase; in the pre-test, 5% of students met the Maximum Completeness Criteria (KKM). 45% of students passed the first cycle test, whereas 100% of students passed the second cycle test. This indicates that using Pow Toon educational materials can help students learn more about English Grammar (simple present tense). Pow Toon learning materials engage students in the learning process, make the subject matter simple to write about and comprehend, and inspire them to use English Grammar (simple present tense) in discussions to explain daily activities.